IMPLEMENTASI KEGIATAN PENGHIJAUAN DALAM PROGRAM REHABILITASI HUTAN DAN LAHAN (RHL) DI KECAMATAN SEKOLAQ DARAT KABUPATEN KUTAI BARAT - Dwi Ery Mujahiddin, Agustinus, Ismail Bakrie, (Universitas 17 Agustus 1945 Samarinda, 2013)
The results showed that, RHL Implementation in West Kutai district is less than optimal because of the lack of supervision, mentoring, and guidance from the relevant agencies so that workers activities less than optimal success. In RHL activities are supported by a variety of factors including supporting Permenhut Number: 76/menhut-II/2008 on Forest Rehabilitation and Reclamation, the potential of land resources, the willingness to improve living standards, and adequate road infrastructure. While inhibiting factor / problem is HR / absence of forestry extension officers, will market certainty timber products from Forest People, and the mindset of the people is still oriented towards projects granted incentives and the ability of administrators manejerial farmer groups is still low.